Building Trust through Lymphatic Filariasis Elimination: A Platform to Address Social Exclusion and Human Rights in the Dominican Republic - Keys, Hunter (Health Hum Rights, 2018)
Hispaniola, the Caribbean island that includes the countries of Haiti and the Dominican Republic (DR), accounts for 90% of lymphatic filariasis (LF) in the Americas. Both countries have committed to LF elimination by 2020. In the DR, LF occurs mainly in bateyes, or company towns that historically hosted migrant laborers from Haiti. A legacy of anti-Haitian discrimination as well as the 2013 Sentencia, which stripped generations of Haitian-descended Dominicans of their citizenship, ensure that this population remains legally, economically, and socially marginalized. Despite this context, the country’s LF elimination program (PELF) has worked in bateyes to eliminate LF through health education and annual drug treatment to interrupt parasite transmission. Based on interviews with batey residents and observations of PELF activities from February–April 2016, this study describes local understandings of social exclusion alongside the PELF community-based approach. The Sentencia reinforced a common perception shared by batey residents: that their lives were unimportant, even unrecognized, in Dominican society. At the same time, the government-run PELF has generated trust in government health activities and partially counteracts some of the effects of social exclusion. These findings suggest that neglected tropical disease (NTD) programs can not only improve the health of marginalized populations, but also create a platform for improving human rights.